A Chinese textbook of Manchu and its Western translations. (4th May 2022) - Gianninoto, Mariarosaria
ABSTRACT: An Introduction to Manchu ( Qīngwén qǐméng 清文啟蒙, 1730) is one of late imperial China's most important Manchu-Chinese bilingual primers. Its third chapter, entitled 'The Manchu Empty Words and Grammatical Particles', is devoted to grammatical description and uses Chinese linguistic categories and terminology to describe Manchu morphology. An Introduction to Manchu was used as a teaching tool for European learners of Chinese and Manchu. Both Wylie and Hoffman adopted a contrastive approach for their English and Italian translations of 'The Manchu Empty Words and Grammatical Particles', in which they added references to Western linguistic categories and comparisons with European languages (Latin, Greek, French, English, Italian). The result was a merging of linguistic paradigms and terminologies. After briefly introducing this bilingual primer, the present paper focuses on the Western translations and presentations of its third chapter. The adaptation of Western and Chinese linguistic categories and terminologies to the description of Manchu is an interesting case of the hybridisation of descriptive categories and the circulation of linguistic knowledge.